Internalisasi Nilai-Nilai Karakter Islam Melalui Pembelajaran Mahfudzot Bahasa Arab dengan Metode Bernyanyi - Nurul Riyatin (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This article aims to increase the understanding and internalization of character values ​​in class B children of RA 'Aisyiyah Tanjungsari through the use of Arabic mahfudzot with the singing method. This research was motivated by children's lack of understanding about the character values ​​being taught, as well as children's lack of interest in learning Arabic. This research was carried out in two cycles, with each cycle including planning, action, observation and reflection. Data was collected through participant observation, in-depth interviews, performance tasks and documentation. The results of the research show that the use of Arabic mahfudzot with the singing method significantly increases children's understanding and internalization of character values. This is shown by the increasing ability of children to explain the meaning of mahfudzot, practice character values ​​in everyday life, and show enthusiasm in learning Arabic.